A novel (E,E)-dioxime and its mono-, di- and trinuclear complexes bearing tetradentate octyl sulfanyl phenylamino substituents. Synthesis, characterization and electrochemical properties of its transition metal complexes - (:unkn) unknown (SPRINGER, 2002)
A new vic-dioxime, 13,14-bis-(hydroxyimino)-9,12,15,18-diazadithiaoctacosane, has been synthesized from 2-octylsulfanylaminobenzene and (E, E')-dichloroglyoxime. Mononuclear transition metal complexes of Ni-II, Cu-II, Co-II and Fe-II have been prepared and were found to have a metal-ligand ratio of 1:2. The synthesis of di- and trinuclear complexes was achieved with (UO2)-O-IV and Cu-II depending on the stoichiometry of the reactants. The complexes were characterized by elemental analysis, H-1-n.m.r., u.v.-vis, i.r., f.a.b.-m.s. and by cyclic voltammetry.
Keywords: SULFUR LIGANDS; VIC-DIOXIME; PHTHALOCYANINES; NICKEL(II); COORDINATION; MONOAZACROWN; COPPER(II); TECHNETIUM; CRYSTAL; OXIMES